Peningkatan dan Efisiensi Operasional Supply Chain Management (SCM) dengan Memanfaatkan Teknologi - M. Asep Rizkiawan; Harry Ramza (Universitas Muhammadiyah Surabaya, 2024)
Abstract- Abstract Supply chain management (SCM) is an integral part of any business that involves the movement of goods and services from one place to another. It covers a wide range of activities, from sourcing raw materials to delivering finished products to customers. However, traditional supply chain management systems are plagued with challenges such as lack of transparency and others. In recent years, emerging technologies such as blockchain, machine learning (ML) and artificial intelligence (AI) have shown promise in improving supply chain management efficiency, security, and transparency. This research investigates the potential of blockchain, machine learning (ML), and artificial intelligence (AI) technologies in improving supply chain management. This paper will summarize the challenges of traditional supply chain management systems and how blockchain, Machine Learning (ML), and Artificial Intelligence (AI) technologies can overcome these challenges. The paper will also evaluate real-life examples of blockchain and Artificial Intelligence (AI) use in supply chain management and their impact on operational efficiency and security. The purpose of this research is to identify the impact of Artificial Intelligence (AI) in supply chain management, the impact of Machine Learning in supply chain management, and the impact of Blockchain in supply chain management. With the results of the study Integrating new technologies such as AI and blockchain in managing supply chains can provide great benefits to organizations. These technologies can increase work efficiency, reduce costs, strengthen the footprint of goods, and increase security. AI can help with predictive analysis, demand forecasting, and automation. Meanwhile, blockchain can provide a guaranteed, open, and secure record for end-to-end tracking, and reduce the risk of fraud and errors. Keywords: Supply chain management 1, Efficiency 2, Technology 3, Blockchain 4, Machine Learning 5, Artificial Intelligence 6